Understanding Factors Impacting on Consumer Satisfaction and Continuance Intention Toward Online Shopping for Residents in Zhanjiang, China - Tang, Chengyi (Scholar: Human Sciences, 2026)
Purpose: This study explored the factors influencing online shopping satisfaction among shoppers in Zhanjiang City, Guangdong Province. A conceptual framework proposes navigability, customer service, tracking, return, trust, customer satisfaction, and continuance intention. Research design, data, and methodology: The scope of this study is to investigate the influencing factors of the residents of 9 districts and counties in Zhanjiang City, Guangdong Province, China, who are all over 18 years old and have rich online shopping experience (at least half a year), and investigate their satisfaction with online shopping platforms and their willingness to continue using them. Confirmatory factor analysis (CFA) and structural equation model (SEM) are used to analyze the data, verify the model’s goodness of fit, and determine the causal relationship between hypothesis test variables. Results: Customer service, tracking, returns, and trust directly and significantly affect customer satisfaction. Customer satisfaction directly and significantly affects the intention to continue. However, in this study, the effect of navigability on customer satisfaction is not significant, so this hypothesis needs to be supported. Conclusions: This study has important theoretical significance and practical value for the sustainable development of online shopping platforms. In particular, it has important theoretical and practical value for improving the user experience of residents using online shopping platforms in various provinces and cities in China.